2018
DOI: 10.2196/10523
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Using a Commercial Fitness Tracker as an Adjunct to Family-Based Weight Management Treatment: Pilot Randomized Trial

Abstract: BackgroundFitness trackers can engage users through automated self-monitoring of physical activity. Studies evaluating the utility of fitness trackers are limited among adolescents, who are often difficult to engage in weight management treatment and are heavy technology users.ObjectiveWe conducted a pilot randomized trial to describe the impact of providing adolescents and caregivers with fitness trackers as an adjunct to treatment in a tertiary care weight management clinic on adolescent fitness tracker sati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(39 citation statements)
references
References 51 publications
1
38
0
Order By: Relevance
“…We found similar barriers among our older group and facilitators among younger participants. Research with a commercial fitness tracker among adolescents with obesity reported a discontinuation rate of 68% before the end of the study that was linked to barriers to physical activity not being addressed by a tracker, seasonality, feelings of activity incompetence, and gradual withdrawal of parental and clinical support [ 42 ]. Our finding that high acceptability of a smartwatch does not translate to adherence is also reported by Phan et al [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found similar barriers among our older group and facilitators among younger participants. Research with a commercial fitness tracker among adolescents with obesity reported a discontinuation rate of 68% before the end of the study that was linked to barriers to physical activity not being addressed by a tracker, seasonality, feelings of activity incompetence, and gradual withdrawal of parental and clinical support [ 42 ]. Our finding that high acceptability of a smartwatch does not translate to adherence is also reported by Phan et al [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research with a commercial fitness tracker among adolescents with obesity reported a discontinuation rate of 68% before the end of the study that was linked to barriers to physical activity not being addressed by a tracker, seasonality, feelings of activity incompetence, and gradual withdrawal of parental and clinical support [ 42 ]. Our finding that high acceptability of a smartwatch does not translate to adherence is also reported by Phan et al [ 42 ]. The physical activity self-monitoring tool available on the smartwatch screen in our study was cited by a number of children and parents as a benefit because they were trying to increase their activity levels.…”
Section: Discussionmentioning
confidence: 99%
“…Among all teens, 42% had searched for fitness and exercise information online and 19% had searched for information on stress and anxiety. Digital technology has been studied as a way to deliver sexual health education (8), weight management (911), physical activity (1214), and nutrition interventions (15, 16), and to enhance medication adherence (17) among adolescents in the general population. Several early studies have highlighted the promise of using technology to address adolescent mental health, including suicide prevention and outreach (18, 19) and treatment for depression and anxiety (20).…”
Section: Introductionmentioning
confidence: 99%
“…Wearable fitness trackers have become a prominent component of the effort in initiating behavioral lifestyle modifications to combat obesity [ 17 , 18 ]. Activity tracking technology has become increasingly prevalent in the United States, with the wearable fitness industry showing exponential growth within the past few years [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wearable devices have demonstrated accuracy with respect to measurements such as heart rate, step count, move distance, and sleep duration; however, accuracy does deteriorate under conditions of increased activity [ 20 , 21 ]. Despite any inaccuracies devices may have, users often report high satisfaction and perception of increased physical fitness [ 17 , 22 ]. The ease of use, increased utilization, and mobility of activity tracking devices has brought about new opportunities for data collection and subsequent research [ 19 , 23 ].…”
Section: Introductionmentioning
confidence: 99%